2000
DOI: 10.1089/152581600419161
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Versus Oral Iron Supplementation for Preoperative Stimulation of Hemoglobin Synthesis Using Recombinant Human Erythropoietin

Abstract: To compare two modalities of iron supplementation for the preoperative stimulation of erythropoiesis using recombinant human erythropoietin (rhEPO), 12 adults in normal hemoglobin and iron status due for elective surgery were randomized to rhEPO 200 U/kg body weight subcutaneously twice weekly combined with either iron sucrose 200 mg intravenously twice weekly or iron sulfate 160 mg/day orally, for 3 weeks preoperatively. Efficacy was measured by the increases over baseline in hemoglobin, reticulocyte count, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 14 publications
0
29
1
1
Order By: Relevance
“…Iron has also been used to improve the efficacy of IV rHuEPO. 23 In a study in only 12 patients comparing administration of 200 mg iron sucrose plus rHuEPO with oral iron, Rohling et al 28 observed no improvement in preoperative Hb levels. In another study, however, concomitant administration of IV iron and rHuEPO in patients with neoplastic disease and iron deficiency anemia improved erythropoietic response and helped maintain body iron stores.…”
Section: Discussionmentioning
confidence: 99%
“…Iron has also been used to improve the efficacy of IV rHuEPO. 23 In a study in only 12 patients comparing administration of 200 mg iron sucrose plus rHuEPO with oral iron, Rohling et al 28 observed no improvement in preoperative Hb levels. In another study, however, concomitant administration of IV iron and rHuEPO in patients with neoplastic disease and iron deficiency anemia improved erythropoietic response and helped maintain body iron stores.…”
Section: Discussionmentioning
confidence: 99%
“…Suplementação de ferro, folato e vitaminas B6, B12 e C são recomendados durante a terapia com eritropoetina, a fim de acelerar a resposta eritropoiética e evitar a depleção dos estoques de ferro. Embora neste relato de caso a estimulação da eritropoiese tenha sido realizada com eritropoetina e ferro oral, a literatura tem demonstrado a superioridade do ferro endovenoso em associação com a eritropoetina (ferro endovenoso 200 mg duas vezes por semana) 8 . Para a administração de ferro endovenoso, recomenda-se a diluição de 100 mg de ferro para 100 ml de solução salina isotônica e uma infusão lenta (1 ml por minuto).…”
Section: Discussionunclassified
“…A very small study in 12 patients with normal Hb and iron status that were due for elective surgery showed no significant difference in Hb increase of patients treated preoperatively with rHuEPO and IS (200 mg iron twice weekly) or ferrous sulfate (160 mg daily for 3 weeks) [67]. However, IS was associated with significantly higher reticulocyte counts and prevented iatrogenic iron depletion.…”
Section: Preoperative Iron Treatmentmentioning
confidence: 98%